Re-viewing Studies on Africa, #Black Lives Matter, and Envisioning the Future of African Studies - Adomako Ampofo, A. (My University, 2016)
This article considers what African Studies needs to look like in order for it to retain its disciplinary relevance for the next generation and in the larger context of the Black Lives movement globally. It asks questions about where we have come from in terms of race consciousness in our discipline and why this issue matters today. It begins by tracing the development of African Studies’ epistemic journey, and follows this with an examination of the recent Black student movements in South Africa and the U.S. It concludes by suggesting where we should be going.
Keywords: Black Lives Matter; Africa; Future